(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Objective:Antibiotics have saved lives worldwide. However, overuse and misuse have led to antibiotic resistance. Antibiotic counseling is a crucial strategy to combat this crisis, promoting responsible use and providing clear information on antibiotics, side effects, and prescribed courses. This study investigates the impact of antibiotic counselling on patient understanding. Method:The study aims to evaluate the effectiveness of antibiotic counseling in promoting responsible antibiotic use and reducing antibiotic resistance. Data will be collected through surveys, involving a diverse patient population and healthcare settings, and analyzed using SPSS.